Azas Kebebasan Berkontrak dalam Perjanjian Keagenan - Gede Agus Wiadnyana; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2021)
In an agency agreement in the form of a standard order, it appears that the parties are not free to jointly determine the contents of the agreement with the principle of freedom of contract. The position of the principal is economically stronger when compared to the agent. This research aims to analyze the principle of freedom of contract in agency agreements. legal protection of agents based on the principle of freedom. The research method uses normative legal research with a library research approach. The legal sources used are primary, secondary, and tertiary legal materials. Technique of calculating or tracing legal materials in the list or grouped, and using methods of noting, recording, quoting, summarizing, and reviewing as needed and written systematically. The result of the research indicates that the principle of freedom of contract has not been fully realized in an agency agreement, considering that the agency agreement is in the form of a standard agreement. The freedom that cannot be realized is the freedom of the parties to determine the form of the agreement and the freedom of the parties to determine the conditions, as well as legal protection for agents who are in a weak position in the agency agreement. namely the law on the business activities of agents. Protection provided by the government's protection for citizens who are agents of commercial competition.